1958
DOI: 10.1113/jphysiol.1958.sp006093
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of frog muscle in hypertonic solutions

Abstract: It is well known that hypertonic solutions diminish, and in sufficient concentration abolish, the twitch of frog muscle, whereas hypotonic solutions within a certain range enhance the twitch (Overton, 1902;Fenn, 1936;Hodgkin & Horowicz, 1957). This paper describes some mechanical measurements made with muscles exposed to solutions up to the equivalent of three times the concentration of normal Ringer's solution, and to hypotanic solutions. METHODSAll the experiments described were made with sartorii of English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

1961
1961
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 16 publications
5
74
0
Order By: Relevance
“…These include administrations of tetracaine, dantrolene Na, Ca 2+ deprivation, and nifedipine (Putney and Bianchi, 1974;Huang, 1981aHuang, , 1990Huang, , 1991Hui, 1983;Bruin, Fitts, Pizarro, and Rios, 1988;Rios and Brum, 1987). The physiological effects of changes in extracellular tonicity have been attributed to changes in intracellular ionic strength arising from the consequent fiber volume change (Howarth, 1958;Dydynska and Wilkie, 1963;Blinks, 1965;Caputo, 1968;Gordon and Godt, 1970). The mechanism for their influence on charge may therefore differ from those of the pharmacological agents.…”
Section: Discussionmentioning
confidence: 99%
“…These include administrations of tetracaine, dantrolene Na, Ca 2+ deprivation, and nifedipine (Putney and Bianchi, 1974;Huang, 1981aHuang, , 1990Huang, , 1991Hui, 1983;Bruin, Fitts, Pizarro, and Rios, 1988;Rios and Brum, 1987). The physiological effects of changes in extracellular tonicity have been attributed to changes in intracellular ionic strength arising from the consequent fiber volume change (Howarth, 1958;Dydynska and Wilkie, 1963;Blinks, 1965;Caputo, 1968;Gordon and Godt, 1970). The mechanism for their influence on charge may therefore differ from those of the pharmacological agents.…”
Section: Discussionmentioning
confidence: 99%
“…The initial release of Ca, presumably from the terminal cisternae, by hypertonic solutions has also been suggested on the basis of the transient contracture (14,51,52,63) and the increase in aequorin signal (94) produced by hypertonicity. Total fiber Ca is not increased, and may be slightly decreased, by hypertonic solutions (14,51), and the increase in the slow component of the exchangeable 45Ca has been interpreted as being due to translocation of Ca into a less readily mobilizable compartment (51).…”
Section: Hypertonic Solutionsmentioning
confidence: 99%
“…Since Hodgkin and Horo-wicz (1957) found that in frog muscle fibers normal action potentials could be observed in hypertonic solutions which abolished twitch tension, a number of workers have tried to identify which step beyond activation in the electrochemical coupling process is blocked by the hypertonic solution. Howarth (1958) suggested that the hypertonic solutions, by causing water movement out of the muscle, concentrated the internal salts and directly affected the interaction of the contractile material, causing a decreased contractile tension. Support for this hypothesis was provided by the studies of April et al (1968) and by us .…”
Section: Introductionmentioning
confidence: 99%